Chad : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper discusses the structure of the financial sector in Chad and describes the key macro-financial linkages. Macro-financial linkages in Chad are driven by a government sector that dominates economic activities in the more modern sectors of the economy, thanks to oil-related revenues. The main macro-financial linkages are indirect through the associated sharp fiscal adjustment and the government's quest for additional financing. Direct credit risks linked to the oil sector appear limited. However, there seems to be a link between declining oil prices and deteriorating banking soundness indicators. The current economic conditions negatively affect private companies dependent on public contracts, potentially hitting the health of banks' loan portfolios.